Boundary crossing between school and university : exploring the possibilities for development in distance teacher education - Þuríður Jóhannsdóttir (2008)
Fyrirlestur haldinn á „Den 10. nordiske læreruddannelseskongres” sem haldin var í Kennaraháskóla Íslands 21.-24. maí 2008 The paper presents a study based on research on the distance education programme for initial teacher education in the Iceland University of Education. The research which is a part of my Ph.D. thesis looks at the distance programme from the perspective of teacher students living and working as teachers in a typical Icelandic coastline district in a sparsely populated region. The purpose of the thesis is to investigate the meaning, importance and possibilities of the programme for teacher students and local schools as well as the importance and possibilities that the connection to the local schools, through the distance students, may open up for the teacher education programme. Development of individuals and the activity systems in which they participate are under consideration.